Blurring Boundaries in Education: Context and Impact of MOOCs - Johan Loeckx (Athabasca University Press, 2016)
The opinions on MOOCs go to extremes, covering a wide variety of topics, affecting economy, pedagogy, and computer science which makes it hard to keep oversight. Despite the many excellent research reports and articles, an overview of the bigger picture, providing a holistic qualitative summary of the different opinions, is still very welcome. Special attention is given to the broader social, cultural, and technological context in which these developments come about. In this paper, it is discussed how the educational industry  has received a “wake up call” provoking a global discussion on learning and teaching, accordingly disturbing established boundaries between formal and informal learning, public and for-profit education, teachers and learners and quite intriguingly, between software and teaching practices. Golden opportunities for Artificial Intelligence and Technology Enhanced Learning are unfolding, evidenced by the digitalization movement of education, gamification, and the stringent need for massively scalable (and therefore computerized) personal learning experiences.